Atividade antioxidante de extratos de própolis: sinergismo, mecanismo de ação e uso em alimentos - Silva, José Dilson Francisco da (2024)
The development of synergistic antioxidant blends of propolis extracts has been considered a strategy to rationalize its use as an ingredient in foods. A synergistic antioxidant blend of green propolis extract (GPE) and brown propolis extract (BPE), in a ratio of 59:41 (% v v-1), was developed in this work. The synergistic blend was designated OPE. Propolis extracts GPE, BPE and OPE presented total phenolic content, g of gallic acid (100 g)-1, of 3.17 ± 0.04, 2.86 ± 0.05 and 2.82 ± 0.02, respectively, and total flavonoid content, g of quercetin (100 g)-1, of 0.75 ± 0.01, 0.62 ± 0.01 and 0.65 ± 0.01, respectively. Regarding the profile of phenolic compounds, -coumaric acid and its respective phenolic derivatives (3,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinic acid, artepillin C, drupanin and baccarin) predominated in the three extracts. The blend showed synergistic antioxidant activity in three models evaluated: one in vitro model and two in situ models (O/W emulsion and pork pâté). In the in vitro model, using the ORAC method, synergism reached values between 31% and 54%. In the O/W emulsion model, the synergistic blend gave the emulsion greater oxidative stability, with a lower peroxide production rate (PV), k = 0.0550 meq L-1 d-1, while the added to the isolated extracts, GPE and PBE, showed higher rates of PV formation, k = 0.0822 meq L-1 d-1 and k = 0.1134 meq L-1 d-1, respectively, therefore synergism is evident in situ between the BPE and GPE extracts. Quantitatively, the in situ synergistic antioxidant effect was about 45%, within the range of results obtained in in vitro studies (31% to 54%). To understand the mechanism of antioxidant action of propolis extracts and the synergistic blend, a kinetic-thermodynamic study of lipid oxidation was carried out in the second in situ model (pork pâté), which was added with extracts. The extracts provided greater oxidative stability to the pâtés than the conventional antioxidant (erythorbate), given the greater inhibition of the formation of lipid oxidation products, peroxide index (PV) and thiobarbituric acid reactive substances (TBARS). The blend also showed antioxidant synergism in the pâtés, as it showed greater efficiency in PV control than isolated extracts. Kinetically and thermodynamically, propolis extracts control lipid oxidation in pâtés by reducing the rate of PV formation (k) and increasing the activation energy (), enthalpy (Δ‡) and Gibbs free energy (Δ‡) of peroxides formation. The peroxide formation in pâtés added with propolis extracts was characterized as a 1st order reaction, endothermic and non-spontaneous. This work demonstrates for the first time the occurrence of in vitro and in situ antioxidant synergism between Brazilian green and brown propolis extracts. The results also provide new information about the mechanism of action of propolis extracts in foods of animal origin, essential for the selection of better conditions for the commercial exploitation of these natural antioxidants.